2016
DOI: 10.1007/s12272-016-0783-z
|View full text |Cite
|
Sign up to set email alerts
|

Britanin attenuates ovalbumin-induced airway inflammation in a murine asthma model

Abstract: We previously demonstrated the alleviation of ovalbumin (OVA)-induced airway inflammation by Inulae flos. In the present study, the effects of britanin, a sesquiterpene compound isolated from Inulae flos, were evaluated in an in vivo animal model for anti-asthma activity through observation of airway hyperresponsiveness (AHR), eosinophil recruitment, Th2 cytokine and IgE levels, and lung histopathology. Britanin administration effectively reduced AHR induced by aerosolized methacholine, airway eosinophilia, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Statistical differences were assessed via the IBM SPSS Statistics v. 19.0.0 (New York, NY, USA) software. The normality of the distributions was evaluated via the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical differences were assessed via the IBM SPSS Statistics v. 19.0.0 (New York, NY, USA) software. The normality of the distributions was evaluated via the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Britanin can also inhibit degranulation and eicosanoid production in IgE/Ag‐induced bone marrow‐derived mast cells, supporting that this may be the mechanism by which it affects allergic inflammation . In a recent report, the therapeutic effect of Britanin on ovalbumin (OVA)‐induced airway inflammation has been demonstrated, corresponding to the anti‐asthma activity of Inulae Flos . In addition to its foreseeable use as an anti‐allergy and anti‐inflammatory agent, Britanin could also protect neural tissue from reperfusion injury following oxygen–glucose deprivation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that limethason notably prevented inflammatory cell infiltration, and was more effective compared with dexamethasone. It is generally accepted that eosinophils are the primary leukocyte to infiltrate in OVA-induced mice ( 25 ). Thus, in the present study, the percentage of different leukocyte types was measured in BALF.…”
Section: Discussionmentioning
confidence: 99%
“…1) is a bioactive sesquiterpene lactone isolated from the aerial portions of Inula lineariifolia (Genus: Inula; Family: Asteraceae) [6]. Previous pharmacological studies of britanin primarily established its antioxidant, anti-inflammation, and cerebroprotective effects [7][8][9][10][11]. However, few studies have been conducted in the anticancer field.…”
Section: Introductionmentioning
confidence: 99%